PERANAN DAN KEWENANGAN KPPU DALAM PERSAINGAN USAHA MINIMARKET - Rafly Rasada, Ruli; Rai Asmara Putra, Dewa Nyoman (Kertha Semaya : Journal Ilmu Hukum; Vol. 02, No. 03, Juni 2014, 2014)
By development of minimarket business that more glow and its development some time break the law, hence it will arise unhealth business competitive among businessman. It cause many development of minimarket. Manimarket is one of modern store with self-supprt service system that sale many kind of goods in retail. Sometimes location of minimarket too near with traditional market then it can make the traditional market is unoperational. This study purpose to find out the role and authorize of business competition observer (KPPU) at minimarket sector. This research type is normative descriptive. This study is literary research. The result showed that by existency commision of business competition observer that have authority as executor in business competitive case, accept complaint from businessman and conduct investigation independently for purpose to overcome minimarket business competition
Keywords: Competition, Minimarket, KPPU